Investigating the Relationship between Pre-service Social Studies Teachers Professional Knowledge and Motivational Orientation in Nigerian Universities - Aghahowa, Bernice Nefeye; Egharevba , John; Iyamu, Ede Sunday (Edukasiana: Jurnal Inovasi Pendidikan, 2024)
This research examines the relationship between the professional knowledge and motivational orientation of prospective Social Studies educators in South-South Nigerian public universities. Employing a survey design, the study encompasses a population of 866 pre-service Social Studies teachers across state and federal universities within the South-South geopolitical zone. A sample of 446 participants was drawn from the population. Data collection involved an achievement test measuring content knowledge and pedagogical content knowledge, alongside a "Social Studies Pre-Service Teachers’ Motivational Orientation Questionnaire" comprising self-efficacy and interest sections. Descriptive statistics including mean and standard deviation addressed the research questions raised in the study, while the hypothesis formulated was analyzed using Pearson Product Moment Correlation (r). Results unveiled a moderate, significantly positive correlation between professional knowledge and motivational orientation among pre-service Social Studies teachers. As an implication, the study underscores the potential predictive utility of professional knowledge in determining motivational orientation. This study makes significant contributions to the existing body of knowledge. One key finding is that pre-service Social Studies teachers in universities located in South-South Nigeria exhibit both high levels of professional knowledge and a strong motivational orientation. Furthermore, the study aligns with prior research by confirming a notable correlation between professional knowledge and motivational orientation.